Reaktualisasi Jihad Perspektif Hadis dalam Konteks ke-Indonesiaan - Ismail, Muhammad; Ismail Ahmad, La Ode; Makmur, Makmur (PAPPASANG, 2023)
Jihad is a word that can inspire great enthusiasm in some people, but on the other hand, it can also instill fear and trauma in others. This is because, in today's context, jihad is often understood by many as a movement of struggle by a minority group of Muslims, which has subsequently created fear among the general public. Jihad is indeed frequently misunderstood, not only by Muslims but also by Western observers who often interpret it as merely a war against non-believers. This research aims to explore the hadiths (sayings and actions of the Prophet Muhammad) about Jihad and explain them by adapting them to the current Indonesian context. Therefore, in this study, a qualitative method is used, where the hadiths related to jihad will be analyzed using descriptive analysis. The results of this research show that in the Indonesian context today, jihad is an effort to strengthen Indonesia in various sectors, such as development and economy, which includes the individual struggles of people to improve their own and their families' well-being. Additionally, education and national character are also essential aspects to be improved so that a correct understanding of Islam can thrive in the midst of society Keywords: Reactualization, Jihad, Hadis